Development of Microbial System to Remediate Reinforced Concrete Structures - Anand, Kamal (My University, 2023)
Utilization of microbially induced calcium carbonate precipitation (MICCP) via biomineralization process has been considered a novel method in self-healing of concrete structures in past decade. To develop MICCP as ready product for field scale construction, mineral-based inoculum of higher shelf life is required. The present study focuses on this aspect of field-based application of MICCP. In this study, mineral admixture (fly ash (FA), silica fume (SF), cement kiln dust (CKD) and rice husk ash (RHA)) based bacterial inoculum were developed to immobilize bacteria in concrete. The prepared inoculums were stored at varying temperatures (4°C and 25°C) and the survival of bacterial cells in carrier-based materials were tested on a weekly basis until 270 days of storage at both temperatures using the plate count method. The cell viability was found to be in the range of 4.5 to 6.0 log cfu/g in FA and SF based inoculum at both the storage temperature even till 180 days of storage. In case of CKD and RHA based inoculum, decline in cell concentration was noted within 90 days of storage at both temperatures indicating CKD and RHA are not suitable as carrier materials. Therefore, only FA and SF based inoculums stored at 4°C were incorporated in concrete to immobilize bacteria and tested for strength and permeation characteristics at the age of 7 and 28 days. In this study, bacterial carrier admixed and bacterial carrier spray treatment of concrete specimens was carried out using nutrient broth, urea and calcium chloride. Results revealed significant improvement of approximately 27% in the compressive strength at 28 days of testing. Also, remarkable reduction in the permeability was observed at 28 days with the incorporation of mineral inoculums. Further, anti-corrosive aspects of FA and SF based inoculum were tested in the chloride environment. Reinforced concrete (RC) specimen containing FA and SF based inoculum as admixed and spray strategy were cast and cured for 28 days in respective curing. These test specimens were then subjected to accelerated current induced corrosion in the chloride environment. The changes occurred due to the corrosion were monitored using well established electrochemical and newly emerging electromechanical impedance (EMI) technique. The results clearly suggested that the FA and SF based carrier material can be effectively used for the corrosion prevention in RC structures and the emerging EMI technique can efficiently monitor the corrosion process. The developed inoculums were tested for the self-healing capabilities in the concrete. The prismatic concrete specimens of 500 × 100 × 100 mm were cast containing FA and SF based inoculum and the crack of approximately 0.5 mm width was generated at the time of casting. After 28 days of water curing, these specimens were dried and the artificial crack width of approximately 0.5mm was healed autonomously using a bacteria-based healing agent (nutrient broth, urea and calcium chloride). The healed cracked surface was examined through optical imaging to monitor the crack width reduction. Along with this, EMI technique was used to monitor the crack healing potential until the full healing of cracked surface was achieved. At the end of test, the healed specimens were subjected to bending failure to assess the strength regain. Significant regain was noticed in healed bacterial specimen (approximately 33 %) in comparison to the control. The healing mineral precipitated inside the cracks was examined through field emission scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD) and thermogravimetric analysis (TGA) to evaluate its physicochemical attributes. The results give clear proof that the FA and SF-based carrier materials can be effectively used in healing the cracks in concrete. Further, to repair existing cracks in concrete structure, bio-cementitious grout were developed using FA and SF inoculums and were tested for fresh and hardened properties. The best performing cementitious bio-grout was used to repair cracks in concrete structures. An attempt was made to develop a procedure for the remediation of cracks in three varying orientations, i.e. horizontal, vertical and inverted, to target actual cracks that might exist in the structures. The performance of the repaired surface was assessed in terms of recovery in flexural strength and water tightness. The mineral composition of the healing product was examined by FESEM-EDX and XRD; results clearly indicated the presence of calcite crystals inside the pores. Also, to quantify the calcium carbonate precipitation in the bio-repaired specimens during curing, EMI technique was employed. Overall, it can be concluded that FA and SF based inoculum can effectively promote MICCP activity to seal the fractured crack of any orientation in existing concrete structures. The best performing bio-grout was then used to repair cracks in actual concrete structures. The cracked location were identified and bio-grout was injected inside the cracked surface. The repaired surface was then cured using growth media supplemented with nutrients. To assess the MICCP activity, EMI technique was employed during the curing period and at the end samples were extracted for microstructural analysis. Results indicated the presence of calcite crystals responsible for the densification of pores.
Ph.D. thesis
Keywords: Bacteria; Reinforced concrete; Corrosion; Self healing; Biogrout